2020
DOI: 10.3389/fpsyg.2020.00493
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Effect of Meaningfulness on the Relationship Between Schizotypy Traits and Suicidality

Abstract: Introduction: Previous studies have found that schizotypy can predict suicide, and that meaningfulness has influential effects on suicidality in the general population. However, it is still not clear whether meaningfulness is associated with suicidality in individuals with schizotypy. The aim of this study was to assess the mediating effects of meaningfulness in the relationship between schizotypy and suicidality. Method: We recruited 2,615 university students (including undergraduates and postgraduates; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Our results showed, in accordance with recent scientific literature, that suicidal ideation scores in high-schizotypal students, and in both genders, were higher than other students (Li et al, 2020;Joiner et al, Joiner Jr. et al, 2001;Kwapil et al, 2013;Teraishi et al, 2014). For instance, a prospective study by Schimanski et al (2017), of New Zealand adolescents (12-17 years) found that those classified as schizotypal showed higher odds of passive suicidal ideation at twoyears follow-up compared to those not schizotypal, even after controlling for depressed affect.…”
Section: Suicidal Ideation and Its Related Factors In The High-schizo...supporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed, in accordance with recent scientific literature, that suicidal ideation scores in high-schizotypal students, and in both genders, were higher than other students (Li et al, 2020;Joiner et al, Joiner Jr. et al, 2001;Kwapil et al, 2013;Teraishi et al, 2014). For instance, a prospective study by Schimanski et al (2017), of New Zealand adolescents (12-17 years) found that those classified as schizotypal showed higher odds of passive suicidal ideation at twoyears follow-up compared to those not schizotypal, even after controlling for depressed affect.…”
Section: Suicidal Ideation and Its Related Factors In The High-schizo...supporting
confidence: 93%
“…However, although suicide prevention interventions targeting vulnerable personality traits may help to reduce suicide rates (Canal‐Rivero et al, 2019), schizotypy has rarely been studied as a suicide risk factor in the existent literature (e.g., Joiner et al, Joiner Jr. et al, 2001; Kwapil et al, 2013). Recently, studies using large student samples (Gong et al, 2020; Li et al, 2020), longitudinal (O'Hare et al, 2021), and twin studies (O'Hare et al, 2020) found that schizotypal personality traits represent risk factors for subsequent suicidal ideation and attempts. Several explanations of the relationship between schizotypal personality traits and suicidality might be suggested, including the fact that these traits are associated with adverse outcomes including impaired cognitive (Noguchi et al, 2008), executive (Gilleen et al, 2020) and social functions (Wang et al, 2013), autistic social/communicative deficits (Zhou et al, 2019), aggression (Seah & Ang, 2008), poor insight (Mısır et al, 2018), emotion dysregulation and depressive symptoms (Gong et al, 2020) in non‐clinical individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this research, the literature shows that meaningful, at the microindividual level, should be associated not only with negative, depressive, and unhealthy experiences, but also with positive and optimistic emotions. As is known, both elements are excellent drivers for enjoying a healthy, joyful life full of subjective well-being, i.e., good living (Li et al, 2020 ). This has a strongly subjective, individual, and relational component (Kok et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study of suicide risk among individuals with schizotypic features has the potential to provide more fine-grained information about the development of suicide risk among individuals with schizophrenia spectrum disorders. The few studies in this area provide support for a relationship between schizotypy and suicide risk (Kwapil et al, 2013; Lentz et al, 2010; Li et al, 2020; Schimanski et al, 2017). Of note, schizotypy is conceptualized as a multidimensional construct with dimensions that align with positive, negative, and disorganized symptoms of schizophrenia (Kwapil & Barrantes-Vidal, 2015; Lenzenweger et al, 1991; Lenzenweger & Dworkin, 1996).…”
mentioning
confidence: 99%